WATAK TOKOH PROTAGONIS DALAM NOVEL PERANG KARYA I GUSTI NGURAH PUTU WIJAYA - Sigit Munanto; Ade Rahima (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2020)
The purpose of this research is to identify the protagonist character. This research explains about literary work which consists of intrinsic and extrinsic element. This research focuses on the protagonist character. This research uses qualitative descriptive approach. The data is taken from the novel Perang by I Gusti Ngurah Putu Wijaya which has ben read clearly. From the data collection, the analysis of the protagonist character are described. Based on the results of data analysis, there are 3 quotations found, they are: 3 quotations of generous aspect, 5 quotations of honesty aspect,  6 quotations of the humble aspect, 5 quotations of defender aspect. From the result of the research, it can be concluded that in the novel Perang by Gusti Ngurah Putu Wijaya, there are four aspects of proragonist character, they are: generous, honesty, humble, and defender.